Foreign Terrorist Fighters (FTF) and State Administration Measures Against Statelessness: Foreign Terrorists Fighters (FTF) Dan Langkah Administrasi Negara Terhadap Keadaan Tanpa Kewarganegaraan - Muttaqim, Muttaqim (Universitas Negeri Semarang, 2020)
One's citizenship as an Indonesian citizen is retested in a situation where a person chooses to leave their country to fight. The choice to leave the country also involves the closest people like family. Indonesia is one of the countries with a large number of Foreign Terrorists Fighter (FTF), FTF from Indonesia also has the potential to re-enter Indonesia. Citizenship status is a Human Rights (HAM) that should be protected by state administration, the rule of law, citizenship status, in this case, is related to the fact that no one can not have citizenship status (stateless) so, the form of state anticipation towards this possibility is all legal instruments and administration which is the solution of various citizens' problems. One example relates to the phenomenon of the citizenship status of ForeignTerrorist Fighters (FTF) and Indonesian families and their rights and obligations